Effect of substrate nano-SiO2 hybridization on edge stress distribution of two-dimensional horseshoe-shaped interconnect under thermal load. (15th October 2020) - Gu, Wanghang; Chen, Cheng; Chen, Rui; Zhao, Hanwei; Liu, Bing
Abstract: The stress distribution of the two-dimensional (2D) horseshoe-shaped interconnect in the flexible electronic composite film under thermal load is reported, and the effect of substrate nano-SiO2 hybridization on this stress distribution is studied. Experimental results show that when the temperature rises, stress concentration gradually occurs at the edge of the 2D horseshoe-shaped interconnect. After nano-SiO2 hybridizing, the stress concentration at the edge is significantly reduced, and the strain stability near the edge is improved. When the substrate SiO2 content is greater than 8 wt%, the negative effect of thermal stress on the composite film is reduced to a very low level.